Biomechanics of the shoulder girdle: a case study on the effects of union rugby tackles - Faria, L.; Campos, B.; Jorge, R. N. (Acta of Bioengineering and Biomechanics, 2017)
Purpose: The shoulder girdle is a complex system, comprised by a kinematic chain and stabilizers. Due to the delicate equilibrium and synchronism between mobility and stability, high external loads may compromise its physiology, increasing the risk of injuries. Thus, this study intends to fully characterize the effects of a rugby tackle on the shoulder`s anatomy and physiology. Methods: For the experimental procedures, a matrix of pressure sensors was used, based on the Teckscan® pressure in-soles, force plates, an isokinetic dynamometer and sEMG (surface electromyography). Results: The anterosuperior region of the shoulder girdle confirmed the highest pressure values during impact (100 kPa-200 kPa). Also, the right and left feet performed a vertical peak force of 1286 N (1.4 BW) and 1998 N (2.21 BW), respectively. The muscular activity of the shoulder muscles decreased after performing multiple tackles. Conclusions: During a tackle, the clavicle, scapula, trapezius and acromioclavicular joint are the anatomical structures with higher risk of injury. Also, the strike force on the feet decreases for stability purposes. After performing multiple impacts the muscular activity of the trapezius and rotator cuff muscles decreases, which may lead, in the long-term, to instability of the shoulder and inefficiency of the scapulohumeral rhythm.